Exploring Shadab Zeest Hashmi’s “THE GREEN WALLS" through Lexical Deviation - Muhammad Wasim Khan; Iqra Malook; Sawera Ishaq; Abdul Karim Khan (University of Chitral Journal of Linguistics and Literature, 2023)
The chief aim of this study is to investigate Shadab Zeest Hashmi’s poem “THE GREEN WALLS” through the level of lexical deviation. The study focuses solely on Code-switching in lexical deviation that is employed to unfold the concealed meanings of the text and to showcase the different layers of meanings that code-switched words carry in this poem. The study is examined by employing the tool of lexical deviation in order to find out how lexical-deviated choices unravel the miserable conditions of child labourers. Therefore, through the use of lexical deviation, the vicious or inhumane attitude and behaviours of the owners, impatience of the customers and owners, the greedy nature of the owners, the payment of a debt in the form of sacrificing life, class distinction, cultural similarities, and new forms of child labour such as forced labour and child soldiers are badly exposed. The study suggests that statistics are alarming all over the world, especially in Pakistan so there is a dire need to take stern measures to eradicate the issue. The study is vital for future scholars as it will encourage them to conduct research in the field of Stylistics because this study is unique regarding its innovative linguistic interpretation. The poetry of Shadab may be explored through various tools such as Cognitive and Feminist Stylistics.